Measuring Agency-Level Results: Lessons Learned from Catholic Relief Services’ Beneficiary and Service Delivery Indicators Initiative - Carr, Harry; Scott, Kelly M. (Journal of MultiDisciplinary Evaluation, 2017)
Background: Many NGOs have less success documenting their results at the agency level than at the program or project level. Little has been published on the challenges NGOs face in developing and measuring agency-level results. To address this issue, InterAction, an alliance of NGOs, commissioned a comparative study that drew on the existing grey literature, and a sample of 17 InterAction member organizations through case studies and interviews. Purpose: This paper builds on that InterAction study by presenting one of the first published case studies of a successful agency-level measurement (ALM) system – Catholic Relief Services’ (CRS’) Beneficiary and Service Delivery Indicators (BSDI) initiative. Setting: A faith-based multi-national relief and development NGO. Intervention: N/A Research Design: A case study approach was used to describe and document the development of the CRS ALM. Data Collection and Analysis: The information in this study is derived primarily from CRS files and documents. Data reflecting ALM practices in other NGOs were derived from the 17 InterAction member NGOs. Data reflecting the ALM practices developed by specific NGOs and presented in tabular form in the paper were derived from official documents published by those NGOs. Findings: The authors discuss key lessons for other large and small organizations to consider when developing their own ALM systems.